Voluntary Disclosures, Corporate Control, and Investment - KUMAR, PRAVEEN; LANGBERG, NISAN; SIVARAMAKRISHNAN, K. (Journal of Accounting Research, 2012)
ABSTRACT We examine the valuation and capital allocation roles of voluntary disclosure when managers have private information regarding the firm’s investment opportunities, but an efficient market for corporate control influences their investment decisions. For managers with long‐term stakes in the firm, the equilibrium disclosure region is two‐tailed: only extreme good news and extreme bad news is disclosed in equilibrium. Moreover, the market’s stock price and investment responses to bad news disclosures are stronger than the responses to good news disclosures, which is consistent with the empirical evidence. We also find that myopic managers are more likely to withhold bad news in good economic times when markets can independently assess expected investment returns.